Primary adrenal insufficiency in children: Diagnosis and management - KIRKGÖZ, TARIK; GÜRAN, TÜLAY (ELSEVIER SCI LTD, 2018)
Primary adrenal insufficiency (PAI) is a life-threatening disorder of adrenal cortex which is characterized by deficient biosynthesis of glucocorticoids, with or without deficiency in mineralocorticoids and adrenal androgens. Typical manifestations of primary adrenal insufficiency include hyperpigmentation, hypotension, hypoglycaemia, hyponatremia with or without hyperkalemia that are generally preceded by nonspecific symptoms at the onset. Recessively inherited monogenic disorders constitute the largest group of primary adrenal insufficiency in children. The diagnostic process of primary adrenal insufficiency includes demonstration of low cortisol concentrations along with high plasma ACTH and identifying the cause of the disorder. Specific molecular diagnosis is achieved in more than 80% of children with PAI by detailed clinical and biochemical characterization integrated with advanced molecular tools. Hormone replacement therapy determined on the type and the severity of deficient adrenocortical hormones is the mainstay of treatment. Optimized methods of steroid hormone delivery, improved monitoring of hormone replacement along with intensive education of patients and families on the rules during intercurrent illness and stress will significantly reduce the morbidity and mortality associated with primary adrenal insufficiency. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: primary adrenal insufficiency; children; steroid hormone; diagnosis; treatment; DUAL-RELEASE HYDROCORTISONE; PLASMA-RENIN ACTIVITY; SHORT SYNACTHEN TEST; 20 YEARS EXPERIENCE; QUALITY-OF-LIFE; FACTOR-I NR5A1; 21-HYDROXYLASE DEFICIENCY; 11-BETA-HYDROXYLASE DEFICIENCY; HYPOGONADOTROPIC HYPOGONADISM; REPLACEMENT REGIMENS